Luminal ions and short chain fatty acids as markers of functional activity of the mucosa in ulcerative colitis. Issue 3 (March 1982) - Roediger, W E; Heyworth, M; Willoughby, P; Piris, J; Moore, A; Truelove, S C
Abstract : Luminal concentrations of short chain fatty acids (SCFA), ammonia, sodium and potassium were measured in colonic dialysate of 16 control subjects and in 65 cases with ulcerative colitis (UC), which were graded according to mucosal changes into mild (1), moderate (2), or severe (3) inflammatory activity. Sodium concentrations were mildly but not significantly increased in severe ulcerative colitis while luminal potassium concentrations were markedly decreased in severe ulcerative colitis (p less than 0.025). Concentrations of SCFA were increased in severe ulcerative colitis. Butyrate concentrations were significantly raised in all stages of active ulcerative colitis even when other fatty acids were not raised. Of all the parameters a lowered pH and raised butyrate concentration most strikingly correlate with the severity of mucosal change. Results indirectly suggest that control of luminal pH, potassium secretion and utilisation of butyrate by the colonic mucosa are impaired with progressive mucosal inflammation.